2021
DOI: 10.2147/prbm.s317961
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Distress Among Ethiopian Pregnant Women During COVID-19: Negative Correlation with Self-Efficacy

Abstract: Background: Since the onset of coronavirus disease 2019, the mental health of individuals has been negatively affected, especially among vulnerable groups. Objective: The aim of this study was to explore the association of psychological distress with self-efficacy and other correlates among Ethiopian pregnant women. Methods: A cross-sectional study was carried out among 384 pregnant women from August 1 to 15, 2020. Pandemic-related psychological distress was measured by the Impact of Event Scale Revised (IES-R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 46 publications
1
15
1
Order By: Relevance
“…Even in the face of financial difficulties, career failure, family discord, or academic failure, they can also get rid of negative emotions by adjusting their cognitive style, changing their original behavior, or seeking help from others [ 40 ]. Some past studies have shown that regulatory emotional self-efficacy is an important indicator of whether an individual can effectively manage their emotional state, and its role is precise to relieve tension, maintain emotional regulation, help regulate emotional impulses and promote mental health [ 41 ]. However, few studies have examined the regulatory emotional self-efficacy and how it impacts the perceived stress in the quantitative method, the current study aims at filling this gap, hence, this study proposed Hypothesis 3.…”
Section: Hypothesesmentioning
confidence: 99%
“…Even in the face of financial difficulties, career failure, family discord, or academic failure, they can also get rid of negative emotions by adjusting their cognitive style, changing their original behavior, or seeking help from others [ 40 ]. Some past studies have shown that regulatory emotional self-efficacy is an important indicator of whether an individual can effectively manage their emotional state, and its role is precise to relieve tension, maintain emotional regulation, help regulate emotional impulses and promote mental health [ 41 ]. However, few studies have examined the regulatory emotional self-efficacy and how it impacts the perceived stress in the quantitative method, the current study aims at filling this gap, hence, this study proposed Hypothesis 3.…”
Section: Hypothesesmentioning
confidence: 99%
“…In their study, the prevalence of general anxiety disorder was 32.2%, a higher rate than was found in China [ 10 ]. Another study in Ethiopia investigated psychological distress and self-efficacy among 384 pregnant women receiving follow-up antenatal care using the Impact of Event Scale Revised (IES-R), Hospital Anxiety and Depression Scale, Generalized Self-Efficacy Scale, and Fear of COVID-19 scale [ 28 ]. The findings of this study indicated severe psychological distress (IES-R scale mean score, 45.1± 17.4).…”
Section: Maternal Mental Health In Africa During the Covid-19 Pandemicmentioning
confidence: 99%
“…The author also found a significant positive association between symptoms of anxiety and depression and fear of COVID-19. However, further analysis revealed that self-efficacy was a protective factor against psychological distress and had a negative association with fear of COVID-19 [ 28 ]. In Ghana, Moyer et al [ 29 ] assessed anxiety and healthcare-seeking behavior among 71 pregnant women using an online survey distributed via social networks.…”
Section: Maternal Mental Health In Africa During the Covid-19 Pandemicmentioning
confidence: 99%
See 1 more Smart Citation
“…The potential impact of the COVID-19 pandemic on mental health should not be overlooked, especially in vulnerable populations like pregnant women. 1 Even under normal circumstances, women are at greater risk of anxiety and depression during pregnancy than at any other time in their lives. 2 Fear of virus transmission to the foetus, social isolation resulting in reduced support from wider family and friend, disruption of maternal health services etc.…”
Section: Introductionmentioning
confidence: 99%